Controlling Fines Migration by Enhancing Fines Attachment using Nanosilica - Shafian et al., Siti Rohaida Mohd (International Journal of Advanced Science and Technology, 2020)
Formation damage in oil reservoirs as a results of fines migration is among a main contribution for productivity decline. Excessive flow rates or pressures can cause the formation fines i.e. clay and/or non-clay migrates, accumulated in the pore throat and caused severe permeability reduction to the formation. This study is aimed to select the best type and optimum concentration of nanosilica, SiO2 in improving the attachment of fines particles on surface of glass beads that mimicked as synthetic porous media. Four types of nanosilica, SiO2 solution prepared in 2.5% NaCl (water based nanosilica W-NSS) and mutual solvents (solvent based nanosilica; E-NSP, E-NSN and E-NSE) were used to treat the glass beads packed with fines through gravity-assisted flow (GAF) test. The amount of fines passing through the treated and untreated glass beads were compared. The laboratory work extensively evaluated the nanosilica, SiO2 attachment on surface of glass beads analysed under Field Scanning Electron Microscopy (FESEM) suggested the optimum nanosilica, SiO2 concentration. Gravity-assisted flow (GAF) test results showed that, glass beads treated with 0.05% SiO2 (E-NSN) improved the fines attachment by 70%. FESEM analysis proved that, the modification of surface of glass beads increased the attraction of fines on the pore surface. Fines migration control using nanosilica can be beneficial in water injection and/or stimulation as it can be found in most non-toxic inorganic materials which also the main component of sandstone, and is more environmental friendly materials compared to chemical based fines stabilizer.